2010
DOI: 10.1002/iub.345
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic responses of thyroid hormone calorigenesis in the liver: Association with oxidative stress

Abstract: SummaryThyroid hormone (L-3,3 0 ,5-triiodothyronine, T 3 ) exerts calorigenic effects by accelerating mitochondrial O 2 consumption through transcriptional activation of respiratory genes, with consequent increased reactive oxygen species (ROS) production. In the liver, ROS generation occurs at different sites of hepatocytes and in the respiratory burst of Kupffer cells, triggering the activation of the transcription factors nuclear factor-jB, signal transducer and activator of transcription 3, and activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 100 publications
1
35
0
Order By: Relevance
“…Tïżœ, n-3 LCPUFA and iron can be considered as hormetic agents [91,92] , which are defined as compounds inducing a dose-response phenomenon characterized by biologically beneficial effects in the low-concentration (dose) range (organ preconditioning) [26][27][28] and harmful responses at high concentrations (doses) or after prolonged exposure (thyrotoxicosis [9ïżœ] , gastrointestinal upset/increase bleeding time [48] and hemochromatosis [94] , respectively). Organ preconditioning by these hormetic agents is not restricted to the liver [26][27][28] , considering that (1) thyroid 1) thyroid ) thyroid hormone-induced preconditioning against IR injury is also observed in the heart [95,96] , with a pattern of protection comparable to that of ischemic preconditioning [97] ; (ïżœ) beneficial effects of n-3 LCPUFA have been dem-ïżœ) beneficial effects of n-3 LCPUFA have been dem-) beneficial effects of n-3 LCPUFA have been demonstrated in rheumatoid arthritis, inflammatory bowel disease, coronary artery disease, asthma and sepsis, conditions with inflammation as a key component of their pathology [48] , in addition to neuroinflammation in all major central nervous system diseases [98] ; and (ïżœ) protec-ïżœ) protec-) protective effects of iron are reported in cardiomyocytes and heart [99][100][101] , oligodendroglia cells [102] and neurones [10ïżœ] .…”
Section: Discussionmentioning
confidence: 99%
“…Tïżœ, n-3 LCPUFA and iron can be considered as hormetic agents [91,92] , which are defined as compounds inducing a dose-response phenomenon characterized by biologically beneficial effects in the low-concentration (dose) range (organ preconditioning) [26][27][28] and harmful responses at high concentrations (doses) or after prolonged exposure (thyrotoxicosis [9ïżœ] , gastrointestinal upset/increase bleeding time [48] and hemochromatosis [94] , respectively). Organ preconditioning by these hormetic agents is not restricted to the liver [26][27][28] , considering that (1) thyroid 1) thyroid ) thyroid hormone-induced preconditioning against IR injury is also observed in the heart [95,96] , with a pattern of protection comparable to that of ischemic preconditioning [97] ; (ïżœ) beneficial effects of n-3 LCPUFA have been dem-ïżœ) beneficial effects of n-3 LCPUFA have been dem-) beneficial effects of n-3 LCPUFA have been demonstrated in rheumatoid arthritis, inflammatory bowel disease, coronary artery disease, asthma and sepsis, conditions with inflammation as a key component of their pathology [48] , in addition to neuroinflammation in all major central nervous system diseases [98] ; and (ïżœ) protec-ïżœ) protec-) protective effects of iron are reported in cardiomyocytes and heart [99][100][101] , oligodendroglia cells [102] and neurones [10ïżœ] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the last three preconditioning strategies have clinical potential, liver preconditioning by thyroid hormone or n-3 long-chain polyunsaturated fatty acids have not been evaluated in man, whereas ischemic preconditioning in human liver resections or in human liver transplantation remains controversial (Videla, 2010). The data presented in this work indicate that Fe administration to rats constitutes an alternate preconditioning strategy that may be of relevance to clinical application, taking into account that repeated injections of 100-125 mg/kg of iron complexes by intramuscular or intravenous routes (100-125 mg/kg, 1-3 times/week for 4-12 weeks) are considered as valid and well tolerated therapeutic strategies in human anemia treatments (Silverstein and Rodgers, 2004;Bayraktar and Bayraktar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous reports have shown that severe hyperthyroidism is associated with increased ROS production and cellular damage. [21][22][23][24][25] Surprisingly, although T 3 has been reported to concurrently induce mitochondrial activity and turnover, 26 the underlying mechanism for their interrelationship is not well understood.…”
Section: Downloaded By [New York University] At 04:05 27 June 2015mentioning
confidence: 99%